KITAB KUNING DAN MADRASAH: STUDI PADA PONDOK PESANTREN HIKMATUSYSYARIEF NW SALUT SELAT LOMBOK BARAT - Abdul Muin (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This study attempts to uncover the education background of Islamic boarding schoolâ€™s educator, the studentsâ€™ motivation levels in studying yellow book and education system of Islamic boarding school. Through the qualitative method, the researcher conducted interviews with key informants, observed the education facilities and activities of the students, as well as studied the Islamic boarding school documents, which then lead to the collection of the data and information related to this research issues. The research result shows: (1) With â€œvery adequateâ€ Islamic boarding school education background, the educators of Hikmatusy syarief Islamic boarding school have successfully maintained and preserved the Islamic boarding school system, especially in studying yellow book with madrasah education system. (2) Most of the students have a strong motivation to study yellow book. (3) Values and elements of the education system of this Islamic boarding school is a single unit that integrated, complete each other and strengthen the implementation of the yellow book learning and madrasah education.